ANALISIS HASIL BELAJAR MAHASISWA PENDIDIKAN BAHASA ARAB UNIVERSITAS MUHAMMADIYAH SETELAH TERINTEGRASI DENGAN MA’HAD AL-BIRR - Nadila, Andi; Masnan, Sulaeman; Amin, Nur Fadilah (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2023)
AbstractThis study aims to determine (1). learning outcomes and (2). factors that influence student learning outcomes in the Arabic Language Education Study Program, Faculty of Islamic Religion, University of Muhammadiyah Makassar, for the 2021/2022 Academic Year after being integrated with Ma'had Al-Birr. Techniques to collect data in the form of interviews and documentation. Data analysis techniques include data reduction, data presentation and data verification. The data sources in this study were students for the 2021/2022 academic year and permanent lecturers of Arabic language education study programs as well as written sources, namely grade transcripts and student cumulative grade point averages or GPA.The results of this study show that: (1) Student learning outcomes that focus on the cumulative grade point average or GPA. Of the 86 active students of the Arabic language education study program for the 2021/2022 academic year, 50% of students have high GPA, 40.70% of students have medium GPA and 9.30% of students have low GPA. (2) The factors that influence student learning outcomes are divided into two:First,Internal factors, students' interest in learning Arabic and previous educational background are very influential.Second,external factors, motivation to learn from the family and friendship environment as well as the university's assessment system which has high standards.Keywords : Student Learning Outcomes, Arabic AbstrakPenelitian ini bertujuan untuk mengetahui (1). hasil belajar dan (2). faktor-faktor yang mempengaruhi hasil belajar Mahasiswa Program Studi Pendidikan Bahasa Arab Fakultas Agama Islam Universitas Muhammadiyah Makassar Tahun Akademik 2021/2022 setelah Terintegrasi dengan Ma’had Al-Birr. Teknik mengumpulan data berupa wawancara dan dokumentasi. Teknik analisis data meliputi, reduksi data, penyajian data dan verifikasi data. Adapun sumber data dalam penelitian ini adalah mahasiswa tahun akademik 2021/2022 dan dosen tetap prodi pendidikan bahasa Arab serta sumber tertulis yaitu transkip nilai dan Indeks prestasi kumulatif mahasiswa atau IPK.Hasil penelitian ini menunjukan bahwa: (1) Hasil belajar mahasiswa yang berfokus pada indeks prestasi kumulatif atau IPK. Dari 86 mahasiswa aktif prodi pendidikan bahasa Arab tahun akademik 2021/2022 terdapat 50% mahasiswa yang memiliki IPK tinggi, 40,70% mahasiswa yang memiliki IPK sedang dan 9,30% mahasiswa yang memiliki IPK rendah. (2) Faktor-faktor yang mempengaruhi hasil belajar mahasiswa terbagi menjadi dua: Pertama, faktor internal, minat belajar bahasa Arab mahasiswa dan latar belakang pendidikan sebelumnya sangat berpengaruh. Kedua, faktor eksternal, motivasi belajar dari lingkungan keluarga dan pertemanan  serta sistem penilaian Universitas yang memiliki standar tinggi.Kata Kunci : Hasil Belajar Mahasiswa, Bahasa Arab